FACTORS OF INFLUENCE OF CAREER SELECTION OF ACCOUNTING STUDENTS AS PUBLIC ACCOUNTANTS IN SHARIA ACCOUNTING DEPARTMENT FACULTY OF ISLAMIC ECONOMIC AND BUSINESS, STATE ISLAMIC INSTITUT TULUNGAGUNG - LANTIP SUSILOWATI BINTI SUWADJI (State Islamic Institute (IAIN) Tulungagung, 2020)
Based on the description from the Ministry of Research and Technology, accounting department is ranked the second most chosen 2017 SBMPTN exam participants after management majors. This happens because the notion of bright future prospects is still inherent in students majoring in accounting. A career in accounting is arguably the dream of many people. Besides having promising prospects, career advancement can be guaranteed. Plus, employment opportunities for the accounting field are very broad and wide open, one of which is as a public accountant who has a broad scope of work. This research uses quantitative approaches with types of descriptive research. The data was collected through a questionnaire method with a purposive sampling technique. The amount of sample used in this study was 130 respondents. Where the responses are students of semester 5 and 7 of Sharia accounting department of the State Islamic Institute Tulungagung. Furthermore, the questionnaire data that has been obtained is subsequently analyzed with multiple linear regression with provisions that have fulfilled the validity test, reliability test and classic assumption Test, then analyzed by T-Test and F-Test. The results of this study indicate that: Professional training and social values results positively and significantly in the career selection of accounting students for public accountants; Professional recognitionand work environment research does not influence this factor does not influence accounting students in choosing a career as a public accountant; Social values ​​are considered as the most dominant factor influencing accounting students in career selection as a public accountant.